Transfer of Low-Molecular Weight Single-Stranded DNA through the Membrane of a High-Flux Dialyzer. Issue 7 (July 2014) - Tao, Xia; Hoenich, Nicholas; Handelman, Samuel K.; Levin, Nathan W.; Kotanko, Peter; Handelman, Garry J.
Purpose: Microbial contamination is often present in dialysate used for hemodialysis. Small single-stranded bacterial DNA sequences are capable of activating human inflammatory pathways, through mechanisms that include the Toll-like-receptor 9, and dialysis patients frequently show severe inflammation. Since these molecules have been found in dialysate and in patients' bloodstreams, we studied the potential of low-molecular weight DNA sequences, of the same structure as found in bacteria, to cross from the dialyzer circuit to the blood circuit of a dialysis filter. Methods: The mass transfer of DNA fragments across a high-flux dialyzer was evaluated with an in vitro dialysis model, in both conventional dialysis and pure convection mode. Measurement of DNA was performed by HPLC. Results: In dialysis mode, these mass transfer coefficients were calculated for different single-stranded DNA chain lengths: 5-bases = 28.5%, 9-bases = 20.5%, 20-bases = 9.4%, 35-bases = 2.4%, 50-bases and 100-bases, no transfer detected. In convection mode, these sieving coefficients were calculated: 5-bases = 1.0, 9-bases = 1.0, 20-bases = 0.68, 35-bases = 0.40, 50-bases = 0.17, 100-bases, no convective transfer detected. The physical size of DNA molecules could be the major factor that influences their movement through dialyzer pores. Conclusions: This study establishes that significant transfer across the dialyzer may occur with singlestranded DNA in the size range of 20-bases or less. These findings need to be confirmed with an in vitro whole blood model and with clinical investigations. Previous studies have described the clinical benefits of achieving high-purity dialysate. Precautions are warranted to minimize the presence of these DNA compounds in fluids utilized for hemodialysis treatment.